A global view of the interplay between non-alcoholic fatty liver disease and diabetes. Issue 4 (April 2022) - Stefan, Norbert; Cusi, Kenneth
Summary: Non-alcoholic fatty liver disease (NAFLD) has become an epidemic, much like other non-communicable diseases (NCDs), such as cancer, obesity, diabetes, and cardiovascular disease. The pathophysiology of NAFLD, particularly involving insulin resistance and subclinical inflammation, is not only closely linked to that of those NCDs but also to a severe course of the communicable disease COVID-19. Genetics alone cannot explain the large increase in the prevalence of NAFLD during the past 2 decades and the increase that is projected for the next decades. Impairment of glucose and lipid metabolic pathways, which has been propelled by the worldwide increase in the prevalence of obesity and type 2 diabetes, is most likely behind the increase in people with NAFLD. As the prevalence of NAFLD varies among subgroups of patients with diabetes and prediabetes identified by cluster analyses, stratification of people with diabetes and prediabetes by major pathological mechanistic pathways might improve the diagnosis of NAFLD and prediction of its progression. In this Review, we aim to understand how diabetes can affect the development of hepatic steatosis and its progression to advanced liver damage. First, we emphasise the extent to which NAFLD and diabetes jointly occur worldwide. Second, we address the major mechanisms that are involved in the pathogenesis of NAFLD and type 2 diabetes, and we discuss whether these mechanisms place NAFLD in an important position to better understand the pathogenesis of NCDs and communicable diseases, such as COVID-19. Third, we address whether this knowledge can be used for personalised treatment of NAFLD in the future. Finally, we discuss the current treatment strategies for people with type 2 diabetes and their effectiveness in treating the spectrum of hepatic diseases from simple steatosis to non-alcoholic steatohepatitis and hepatic fibrosis.